A Look at the Sky of the Wichi - Mariani, Mauro (2017)
We present a brief bibliographic report highlighting the significance of the readings of the sky by the different Wichi groups inhabiting the Chaco region. A number of celestial objects and related myths are described. Furthermore, we provide a series of examples concerning the relationship between some celestial objects and the various beings populating the Wichi cosmos, on the one hand, and Wichi social organisation and their culture on the other. In addition, we stress the need to continue investigating, especially doing ethnographic fieldwork to update and challenge the existing research.